The Cordilleran Ice Sheet in Northern British Colombia - Ryder, June; Maynard, Denny (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1991)
ABSTRACTDates from lavas associated with tills and erratics indicate that ice-sheet glaciations occurred between 4 and 0.6 Ma BP. The few radiocarbon dates that are available suggest that the chronology of the Late Wisconsinan (Fraser Glaciation) ice sheet of northern British Columbia was similar to that of the southern part of the province. During what may have been a long, early phase of this glaciation, Glacial Lake Stikine was dammed by advancing valley glaciers in the Coast Mountains, and alpine glaciers developed on the intermontane plateau. At the climax of Fraser Glaciation, ice-flow patterns were dominated by outflow from a névé centred over the northern Skeena Mountains. Déglaciation occurred partly by frontal retreat of ice tongues and partly by downwasting of stagnant ice. Recessional moraines mark one or more resurgences or stillstands of the ice margin. During déglaciation, Stikine River valley was occupied by an active outlet glacier and a major subglacial drainage system.